Pandemic Democracy: Impact Regional Elections Held During the COVID-19 Pandemic - Muhammad Habibi (Mengeja Indonesia Publisher, 2021)
This article describes the impact of regional head elections held during the Covid-19 pandemic. It starts with an explanation of why elections are essential in a democracy. The approach used in this research is a literature study used primarily to explain the country's ability to hold elections, about how the risks to democracy are in the presence of external threats such as that experienced by the world with the spread of COVID-19. This study states that the pandemic is one factor that puts pressure on the global democracy index, Including Indonesia, in 2020. The incumbent's abuse of power in favoring himself as a candidate who will participate in the contestation includes the politicization of the Covid-19 social assistance incumbent candidate.